Macrolactin A mediated biocontrol of Fusarium oxysporum and Rhizoctonia solani infestation on Amaranthus hypochondriacus by Bacillus subtilis BS-58 - Pandey, Chitra; Prabha, Deepti; Negi, Yogesh Kumar; Maheshwari, Dinesh Kumar; Dheeman, Shrivardhan; Gupta, Monika (Frontiers in Microbiology, 2023)
Plant diseases are one of the main hurdles for successful crop production and sustainable agriculture development world-wide. Though several chemical measures are available to manage crop diseases, many of them have serious side effects on humans, animals and the environment. Therefore, the use of such chemicals must be limited by using effective and eco-friendly alternatives. In view of the same, we found a Bacillus subtilis BS-58 as a good antagonist towards the two most devastating phytopathogens, i.e. Fusarium oxysporum and Rhizoctonia solani. Both the pathogens attack several agricultural crops (including amaranth) and induce a variety of infections in them. The findings of scanning electron microscopy (SEM) in this study suggested that B. subtilis BS-58 could inhibit the growth of both the pathogenic fungi by various means such as perforation, cell wall lysis, and cytoplasmic disintegration in the fungal hyphae. Thin-layer chromatography, LC-MS and FT-IR data revealed the antifungal metabolite to be macrolactin A with a molecular weight of 402. Presence of the mln gene in the bacterial genome further endorsed that the antifungal metabolite produced by BS-58 was macrolactin A. Pot trial conducted in the present study showed that seed treatment by BS-58 effectively reduced seedling mortality (54.00 % and 43.76 %) in amaranth, when grown in pathogen infested soil (F. oxysporum and R. solani, respectively), when compared to their respective negative controls. Data also revealed that the disease suppression ability of BS-58 was almost equivalent to the recommended fungicide, carbendazim. SEM analysis of roots of the seedlings recovered from pathogenic attack substantiated the hyphal disintegration by BS-58 and prevention of amaranth crop. The findings of this study conclude that macrolactin A produced by B. subtilis BS-58 is responsible for the inhibition of both the phytopathogens and the suppression of the diseases caused by them. Being native and target specific, such strains under suitable conditions, may result in ample production of antibiotic and better suppression the disease.